A World of Turmoil The United States, China, and Taiwan in the Long Cold War - Hartnett, Stephen J. (Book collections on Project MUSE., 2021)
"A World of Turmoil offers case studies of five critical moments: the end of World War II and the start of the Long Cold War; the almost-nuclear war over the Quemoy Islands in 1954-1955; the detente, deceptions, and denials surrounding the 1972 Shanghai Communique; the Taiwan Strait Crisis of 1995-1996; and the rise of postcolonial nationalism in contemporary Taiwan"--